Towards the understanding of chloride profiles in marine exposed concrete, impact of leaching and moisture content. (1st September 2016) - De Weerdt, Klaartje; Orsáková, Denisa; Müller, Arnaud C.A.; Larsen, Claus K.; Pedersen, Bård; Geiker, Mette R.
Abstract: Cores drilled from three concrete beams submerged in sea water for 16 years at the South Western Norwegian coast were examined. The beams were cast with different binders containing Portland cement and silica fume, fly ash or slag and with water-to-binder ratios (w/b) between 0.40 and 0.44. The aim of the study was to investigate whether the binder composition would affect the elemental changes in the concrete caused by the exposure to sea water and thereby the chloride ingress. No large differences were observed. All concretes showed a 200–300 μm deep magnesium enriched zone containing negligible amounts of sulphur and chlorine at the surface. This zone was followed by a sulphur enriched zone (2–5 mm deep), which then again partially overlapped with a following chlorine enriched zone (approximately 50 mm deep). For all three concretes, moisture measurements showed that the core of the concrete beams was not saturated, indicating self-desiccation and low pore connectivity. The absence of a considerable difference in chloride ingress for the investigated concretes, indicates either that the replacement levels of the Portland cement are too low to have a marked effect on the chemistry, or that the ingress of chloride is mainly governed by comparable physical properties i.e. porosity and degree of saturation.